1997
DOI: 10.1021/ma960548j
|View full text |Cite
|
Sign up to set email alerts
|

Polyion Complex Langmuir−Blodgett Layers Containing an Ionic Water-Soluble Polysilane

Abstract: Monolayers of anionic amphiphiles, arachidic acid (C19COOH) and a double long chain sulfonic acid derivative (2C12SO3Na), were spread on the water subphase containing an ammonium-containing polysilane (APS), and Langmuir−Blodgett (LB) films from these polyion complex monolayers were prepared. Single layer deposition of these polyion complex monolayers was successfully achieved onto a hydrophilic substrate under all conditions examined, but multilayers could be prepared under limited conditions in the Z-type mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The secondharmonic intensity, however, was found to increase only slightly with a 5-fold increase in the number of deposited layers, and these authors concluded that although deposited as Z-type films, molecular rearrangement to a symmetric structure occurs during the dipping process. Seki et al 25 and Pen ˜acorada et al 29 similarly concluded from X-ray measurements that LB films of polyioncomplexed arachidic acid initially deposited as either Z-type or X-type multilayers invert to Y-type bilayers upon aging.…”
Section: Introductionmentioning
confidence: 99%
“…The secondharmonic intensity, however, was found to increase only slightly with a 5-fold increase in the number of deposited layers, and these authors concluded that although deposited as Z-type films, molecular rearrangement to a symmetric structure occurs during the dipping process. Seki et al 25 and Pen ˜acorada et al 29 similarly concluded from X-ray measurements that LB films of polyioncomplexed arachidic acid initially deposited as either Z-type or X-type multilayers invert to Y-type bilayers upon aging.…”
Section: Introductionmentioning
confidence: 99%
“…Surface pressure plateaus, like those observed in the compression isotherms of Figure , have been reported for a number of similar polyion-complexed systems 7,9,10,21,26,39 as well as for cellulose derivatives containing covalently attached hydrophobic side chains. , The plateau has been ascribed to a transition from an expanded to a condensed monolayer, , a fluid−solid transition, the formation of a discrete bilayer, the nonspecific removal of material from the surface, or collapse . It is, in fact, probable that the exact nature of the phase transition responsible for the plateau differs for the various systems.…”
Section: Resultsmentioning
confidence: 57%
“…The K a value of acid molecules condensed in two dimensions shifts to the basic side due to the strong electrostatic interaction between the molecules. 23,24 Moreover, the K a value of a monolayer can be determined by the dependence of the molecular area of the monolayer on the subphase pH. 25 To obtain the pK a value of the p(DDA/AA49) monolayer, the copolymer was spread on water subphases with The film was prepared using the p(DDA/AA49) copolymer for subphase pH 5.9, 7.0, and 10 and the p(DDA/AA47) copolymer for subphase pH 7.9 and 9.1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%